Kelayakan Instrumen TOAFL sebagai Alat Ukur Kemampuan Membaca Mahasiswa Fakultas Ilmu Pendidikan - Hakiem, Marsekal Rahman; Abdurrohman, Muhammad Uwais; Faturrahman, Muhammad Irfan (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Evaluation of Arabic language learning requires a valid and reliable instrument to measure students' abilities accurately. This study aims to analyze the feasibility of the ITMAM (Ikhtibar Tahdid Mustawa al-'Arabiyyah lil Muta'allimin) instrument as a measuring tool for the Arabic reading skills of STITMA Yogyakarta students. The research method uses a descriptive quantitative approach by analyzing 60 questions tested on 311 students using SPSS version 25 software to test validity, reliability, level of difficulty and discriminatory power. Analysis is needed to ensure the quality of the test instrument that can provide accurate measurement results and become the basis for effective learning evaluation. The results showed that all questions were valid and reliable, with 65% having a moderate difficulty level, 37.7% at an easy level and 3.3% at a difficult level. The results of the Discriminatory Power Test showed that 60% of the questions were accepted well and 40% needed revision so the ITMAM instrument is suitable for use as a standard evaluation tool for Arabic reading ability with several improvements to certain questions.